2016
DOI: 10.1134/s1607672916050045
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the size of membrane microparticles of different cellular origin by dynamic light scattering

Abstract: Size of membrane microparticles (MPs) from blood plasma and MPs produced in vitro by activated endothelial cells (ECs), monocytes, THP-1 monocytic cells, granulocytes, and platelets was evaluated by dynamic light scattering. MPs were sedimented from the culture media, cell supernatants, and plasma at 20 000 g for 30 min. Average diameters of all types of MPs ranged from 300 to 600 nm. Plasma MPs had the smallest size. Close sizes were registered for MPs from platelets and THP-1 cells. MPs from monocytes were l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 7 publications
0
7
0
4
Order By: Relevance
“…Variations in the percentage of annexin V-positive MPs could be at least partially explained by the difference in MPs size. Earlier, using the dynamic light scattering method, for the MPs sizing, we have shown in direct comparative studies that ErMPs have an average diameter of 200-250 nm, PMPs 350-400 nm, EMPs and THP MPs 400-500 nm, and EMPs 550-600 nm [29,30,47]. We presumed that annexin V-FITC binding to small MPs was too low to provide FITC signals above the threshold noise level, which is why we measured the different percentages of annexin V-positive events in samples of MPs of different origins with different average sizes.…”
Section: Discussionmentioning
confidence: 99%
“…Variations in the percentage of annexin V-positive MPs could be at least partially explained by the difference in MPs size. Earlier, using the dynamic light scattering method, for the MPs sizing, we have shown in direct comparative studies that ErMPs have an average diameter of 200-250 nm, PMPs 350-400 nm, EMPs and THP MPs 400-500 nm, and EMPs 550-600 nm [29,30,47]. We presumed that annexin V-FITC binding to small MPs was too low to provide FITC signals above the threshold noise level, which is why we measured the different percentages of annexin V-positive events in samples of MPs of different origins with different average sizes.…”
Section: Discussionmentioning
confidence: 99%
“…MPs were also collected from the culture media, cell supernatants, and plasma by centrifugation at 20,000 g for 30 min. The average diameter of all types of MVs was varying much comparing different reports [19,[23][24][25]. The plasma MPs had the smallest size similar to MPs released from platelets and THP-1 cells, while MPs from monocytes were larger, and MPs from granulocytes and ECs were the largest ones.…”
Section: Introductionmentioning
confidence: 88%
“…The plasma MPs had the smallest size similar to MPs released from platelets and THP-1 cells, while MPs from monocytes were larger, and MPs from granulocytes and ECs were the largest ones. The data obtained from various reports indicate that the size of membrane MPs depends on the type of the cells from which they originate [23]. Although MVs have been discovered for years, the understanding of the mechanism of the formation as well as the biological roles of MVs is still a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that diversified types of cells, including RBCs, endothelial cells, monocytes, granulocytes, and platelets, release EVs. Additionally, EVs can be isolated by various methods from cell culture media, plasma, and other biofluids [23,41,70,71]. Although several research groups have demonstrated the advantages of using EVs for RNA delivery, there are still issues with EVs generated from fibroblasts and dendritic cells being not permanently available from all subjects [69,72].…”
Section: Advantages Of Red Blood Cell Extracellular Vesicles In Theramentioning
confidence: 99%